Hydrogen sulphide, a novel gasotransmitter involved in guard cell signalling - Garcia Mata, Carlos (2010)
•Hydrogen sulphide (H2S) has been proposed as the third gasotransmitter. In animal cells, H2S has been implicated in several physiological processes. H2S is endogenously synthesized in both animals and plants by enzymes with l-Cys desulphydrase activity in the conversion of l-Cys to H2S, pyruvate and ammonia. •The participation of H2S in both stomatal movement regulation and abscisic acid (ABA)-dependent induction of stomatal closure was studied in epidermal strips of three plant species (Vicia faba, Arabidopsis thaliana and Impatiens walleriana). The effect of H2S on stomatal movement was contrasted with leaf relative water content (RWC) measurements of whole plants subjected to water stress. •In this work we report that exogenous H2S induces stomatal closure and this effect is impaired by the ATP-binding cassette (ABC) transporter inhibitor glibenclamide; scavenging H2S or inhibition of the enzyme responsible for endogenous H2S synthesis partially blocks ABA-dependent stomatal closure; and H2S treatment increases RWC and protects plants against drought stress. •Our results indicate that H2S induces stomatal closure and participates in ABA-dependent signalling, possibly through the regulation of ABC transporters in guard cells.